Coaching and Doping: A Test of Situational Action Theory - Shadmanfaat, Seyyedeh Masoomeh (Journal of drug issues, 2024)
Deviant and criminal behavior in sport remains a significant problem because it threatens the rules, norms and culture that value fairness. The use of performance-enhancing substances (PED), also known as “doping”, is generally prohibited in sanctioned sports because they violate this philosophy. While previous research has documented the crucial role that coaches occupy in player’s deviancy, there is a lack of theoretical perspectives used to assess the relationship between coaches and athletes in decisions to engage in doping. The present study examines a sample of Iranian sports coaches (n = 374) using situational action theory and regression models. The results indicate that deviant coaching is a form of moral action that involves an interaction between characteristics of the coach.